Delayed diagnosis of adult indolent systemic mastocytosis - Carsten Sauer Mikkelsen; Andrew Nybo; Kristian Bakke Arvesen; Johan Holk-Poulsen (PAGEPress Publications, 2014)
Systemic mastocytosis (SM) is a rare, heterogeneous disorder characterized by infiltration and accumulation of mast cells within multiple organs, most commonly the skin. Given the rarity of the disease and the fact that many of its symptoms are shared by more common disorders, a diagnosis may be delayed or hindered. These patients have an elevated risk of developing potentially life-threatening anaphylactoid reactions, thus underscoring the importance of keeping SM in mind as a differential diagnosis when a patient presents with chronic, itchy skin lesions and a history of multiple allergic reactions to bites, drugs, and anesthesia. We present a case illustrating that features of SM common to many disorders may hinder or delay its diagnosis.